The Liberal Self : John Stuart Mill's Moral and Political Theory - Donner, Wendy, 1948- (Book collections on Project MUSE., 1991)
Wendy Donner contends here that recent commentators on John Stuart Mill's thought have focused on his notions of right and obligation and have not paid as much attention to his notion of the good. Mill, she maintains, rejects the quantitative hedonism of Bentham's philosophy in favor of an expanded qualitative version. In this book she provides an account of his complex views of the good and the ways in which these views unify his moral and political thought.